2019
DOI: 10.2298/soc1904631m
|View full text |Cite
|
Sign up to set email alerts
|

Online weak ties, a sign of a diaspora in-the-making? The case of the Malagasy abroad

Abstract: Internet 2.0 fosters the emergence, connection and association of a geographically dispersed community such as Malagasy migrants. This exploratory study analyses Malagasy online practices as a means to understanding the social dynamics and community-building in their host countries. The method employed relies on a parallel analysis of 121 websites and 82 Facebook public pages and groups created and/or managed by Malagasy migrants. The websites are classified according to the category of their activity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that Malagasy migrants in France use online platforms as tools for community building and for displaying their shared and common identity (Andrianimanana and Roca-Cuberes 2019;Rakotoary 2019). In line with these studies, this paper focuses on the online social dynamics of these Malagasy migrants, who have mostly been studied through analyses of their offline activities in the existing literature.…”
Section: An Overview Of Malagasy Migrant Communities In Francementioning
confidence: 99%
“…Recent studies have shown that Malagasy migrants in France use online platforms as tools for community building and for displaying their shared and common identity (Andrianimanana and Roca-Cuberes 2019;Rakotoary 2019). In line with these studies, this paper focuses on the online social dynamics of these Malagasy migrants, who have mostly been studied through analyses of their offline activities in the existing literature.…”
Section: An Overview Of Malagasy Migrant Communities In Francementioning
confidence: 99%